Issues and solutions in air-traffic infrastructure and flow management for sustainable aviation growth: a literature review. (24th October 2019) - An, Heungjo; King, Nelson; Hwang, Sung Ook
The demand for air transportation has continuously increased over the past few decades and is expected to grow at 2% per annum over the next 20 years. However, airspace is physically limited, and expanding even the ground infrastructure may be insufficient to meet this demand. In order to investigate issues associated with overcoming the limited air-traffic resources, this paper systematically reviews literature on the air-traffic system with a particular focus on both air and ground infrastructure management. First, major issues in the air-traffic system, problem structures, and solution methods were characterised and categorised. This showed that the air-traffic system is transitioning from addressing static, complicated, and large-scale problems to variability, event-propagation, uncertainties, and integration of several areas. Finally, necessary and promising future research topics are proposed for sustainable aviation growth.